Application of Group Guidance Service in Improving English Communication of Young Mosque Activist - Yandri, Hengki; Juliawati, Dosi; Musdizal, Musdizal (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2019)
This research was conducted because of the problems of young mosque activists that did not use English communication correctly. The purpose of this research was to increase the English communication of young mosque activists using Group Guidance Service. The research design was pre-experiment: the one group pretest-posttest that conduct on ten young mosque activists. This research used the liker scale in checklist form, and the research results were analyzed using the Wilcoxon Signed Ranks Test formula. The result of this research found that there were significant differences in English communication of young mosque activists before and after the treatment using group guidance services